Strategic conditions of appropriation of the uses of Information and Communication Technologies (ICT) for the access to the information society. Case of French-speaking Africa: Cameroon, Gabon and Senegal. - (:unkn) unknown (My University, 2008)
The fast progress of the technology of the communications and transport, which cause a drop in the costs of the goods, the capital, the people and the information, supported the emergence of the information society, thanks to the speed to which information is gathered and transmitted. The reality of this society in many countries all over the world allowed UNESCO and the UNCSTD (United Nations Center for Science and Technology for Development) to establish criteria making it possible to measure its state and its evolution. French-speaking Africa, territory of our study, appears there late because of many obstacles: technological, political and institutional, legal and ethical, sociocultural and financial. This has as a consequence an insufficient integration of the ICT in socio-economic, educational, and public administration's contexts. But, the role of the ICT like factor of development, which should result in the installation of new competences into French-speaking Africa, appears still limited by the lack of qualified human resources. If the reasons of this explanation are sought, one can find them in the deficit of the public investments and deprived, which raises the question of the public policies. Our work consists first of all, to examine the action of the public policies in the introduction of an information society in French-speaking Africa and, secondary, to determine the strategic conditions (means) to take into account so that an appropriation of the uses of the ICT by the citizens of French-speaking Africa develops, for the access of this area of the world to the information society.
Keywords: African Research